Mutual influences of pain and emotional face processing - Wieser, Matthias J.; Gerdes, Antje B. M.; Reicherts, Philipp; Pauli, Paul (Frontiers in Psychology, 2014)
The perception of unpleasant stimuli enhances whereas the perception of pleasant stimuli decreases pain perception. In contrast, the effects of pain on the processing of emotional stimuli are much less known. Especially given the recent interest in facial expressions of pain as a special category of emotional stimuli, a main topic in this research line is the mutual influence of pain and facial expression processing. Therefore, in this mini-review we selectively summarize research on the effects of emotional stimuli on pain, but more extensively turn to the opposite direction namely how pain influences concurrent processing of affective stimuli such as facial expressions. Based on the motivational priming theory one may hypothesize that the perception of pain enhances the processing of unpleasant stimuli and decreases the processing of pleasant stimuli. This review reveals that the literature is only partly consistent with this assumption: Pain reduces the processing of pleasant pictures and happy facial expressions, but does not - or only partly - affect processing of unpleasant pictures. However, it was demonstrated that pain selectively enhances the processing of facial expressions if these are pain-related (i.e. facial expressions of pain). Extending a mere affective modulation theory, the latter results suggest pain-specific effects which may be explained by the perception-action model of empathy. Together, these results underscore the important mutual influence of pain and emotional face processing.